Environmental Impacts on Skin Microbiomes of Sympatric High Arctic Salmonids - Erin F. Hamilton; Collin L. Juurakko; Katja Engel; Josh D. Neufeld; John M. Casselman; Charles W. Greer; Virginia K. Walker (Fishes, 2023)
In the region of King William Island, Nunavut, in the Canadian high Arctic, populations of salmonids including Arctic char (Salvelinus alpinus), cisco (Coregonus autumnalis and C. sardinella) as well as lake whitefish (C. clupeaformis) are diadromous, overwintering in freshwater and transitioning to saline waters following ice melt. Since these fish were sampled at the same time and from the same traditional fishing sites, comparison of their skin structures, as revealed by 16S rRNA gene sequencing, has allowed an assessment of influences on wild fish bacterial communities. Arctic char skin microbiota underwent turnover in different seasonal habitats, but these striking differences in dispersion and diversity metrics, as well as prominent taxa involving primarily Proteobacteria and Firmicutes, were less apparent in the sympatric salmonids. Not only do these results refute the hypothesis that skin communities, for the most part, reflect water microbiota, but they also indicate that differential recruitment of bacteria is influenced by the host genome and physiology. In comparison to the well-adapted Arctic char, lake whitefish at the northern edge of their range may be particularly vulnerable, and we suggest the use of skin microbiomes as a supplemental tool to monitor a sustainable Indigenous salmonid harvest during this period of change in the high Arctic.